Quantitative examination of video-recorded NHS Health Checks: comparison of the use of QRISK2 versus JBS3 cardiovascular risk calculators. Issue 9 (25th September 2020) - Gidlow, Christopher J; Ellis, Naomi J; Cowap, Lisa; Riley, Victoria A; Crone, Diane; Cottrell, Elizabeth; Grogan, Sarah; Chambers, Ruth; Clark-Carter, David
Abstract : Objectives: Quantitatively examine the content of National Health Service Health Check (NHSHC), patient–practitioner communication balance and differences when using QRISK2 versus JBS3 cardiovascular disease (CVD) risk calculators. Design: RIsk COmmunication in NHSHC was a qualitative study with quantitative process evaluation, comparing NHSHC using QRISK2 or JBS3. We present data from the quantitative process evaluation. Setting and participants: Twelve general practices in the West Midlands (England) conducted NHSHC using JBS3 or QRISK2 (6/group). Patients were eligible for NHSHC based on national criteria (aged 40–74, no existing cardiovascular-related diagnoses, not taking statins). Recruitment was stratified by patients' age, gender and ethnicity. Methods: Video recordings of NHSHC were coded, second-by-second, to quantify who was speaking and what was being discussed. Outcomes included consultation duration, practitioner verbal dominance (ratio of practitioner:patient speaking time (pr:pt ratio)) and proportion of time discussing CVD risk, risk factors and risk management. Results: 173 video-recorded NHSHC were analysed (73 QRISK, 100 JBS3). The sample was 51% women, 83% white British, with approximately equal proportions across age groups. NHSHC duration varied greatly (6.8–38.0 min). Most (60%) lasted less than 20 min. On average, CVD risk was discussed for less than 2 min (9.06%±4.30% of consultation time). There were indications that, compared with NHSHC using JBS3, those with QRISK2 involved less CVD risk discussion (JBS3 M=10.24%, CI: 8.01–12.48 vs QRISK2 M=7.44%, CI: 5.29–9.58) and were more verbally dominated by practitioners (pr:pt ratio JBS3 M=3.21%, CI: 2.44–3.97 vs QRISK2=2.35%, CI: 1.89–2.81). The largest proportion of NHSHC time was spent discussing causal risk factors (M=37.54%, CI: 32.92–42.17). Conclusions: There was wide variation in NHSHC duration. Many were short and practitioner-dominated, with little time discussing CVD risk. JBS3 appears to extend CVD risk discussion and patient contribution. Qualitative examination of how it is used is necessary to fully understand the potential benefits of these differences. Trial registration number: ISRCTN10443908 .